Feminists' viewpoints on the female celebrities’ sexualization in the United States: 1980s-present = Quan điểm của các nhà hoạt động nữ quyền về hiện tượng tình dục hóa của các ngôi sao nữ tại Hoa Kỳ từ năm 1980 đến nay - Lê, Thanh Hà (2020)
The sexualization of numerous female celebrities has been in the spotlight in the recent years. Reasons for the issue might vary. The media and popular culture together with the widespread of the press, the Internet and cable television make it advantageous for pop stars to get sexualized. Capitalism and individualism fuel the situation. And empowerment women or for the sake of “feminism” become a perfect explaination for female stars’ overexposed images on stage as well as daily life. The question is whether or not feminism – a historical wave since the 1960s to liberate women - plays any part in the sexualization of modern-day female celebrities. The research examined a number of examples in the period from the 1980s to present day to prove the sexualization of female stars and look at opinions of both feminists and the celebrities on the issue. This is a secondary research, in which opinions were collected, sompared, contrasted and carefully synthesized to see whether it was because of feminism that situated the sexualization of female stars or it was just an excuse for celebrities to achieve fame and prosperity.